Energy Harvesters and Self-Powered Sensors for Smart Electronics, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint is a collection of articles in the Special Issue "Energy Harvesters and Self-Powered Sensors for Smart Electronics, 2nd Edition", published in Micromachines, containing one Editorial, nine original research articles, and one review article. This reprint showcases the latest progress in the field of energy harvesting and self-powered sensing for enabling a wide range of advanced applications in the era of the Internet of Things, digital health, and metaverse. With broad coverage and deep insights into technology innovations, this reprint can provide readers with detailed design considerations and actual implementations of various energy-harvesting devices and systems, inspiring new ideas to enable the sustainable development and transformation of our society.